2019
DOI: 10.25130/tjes.26.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Mixture of (Concrete Waste and Asphalt Waste) on the Properties of Gypseous Soil

Abstract: Gypseous soil which is used is taken from Tikrit city in Salah Aldeen government and specially from Tikrit University from a depth (1.5-2)m, It’s type is sandy gravely with a small percentage of silt and clay while the percentage of gypsum is (34-36)%, The tests on soil is standard proctor compaction, direct shear, collapsibility and California bearing ratio. The number of samples is (70). The effect of adding concrete waste (2, 4, 6 and 8%) and waste of Asphalt mixture (2, 4, 6 and 8) % on dry soil, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…al. [10] used the mixture of (concrete waste and asphalt waste) as addition to the gypseous soil, they found that, the values of cohesion and angle of internal friction increase with the increase of concrete wastes, in which the cohesion increases in a magnitude of 100% and angle of internal friction in a magnitude of 14%, the value 8% represents the optimum percentages. When asphalt mixture wastes are added, the cohesion increases in a magnitude of 112% with a decrease in the angle of internal friction in a magnitude of 2% and the optimum percentage is 108% with an increase in the angle of internal friction in a magnitude of 14%.…”
Section: Plate (1) Individual Footingsmentioning
confidence: 99%
“…al. [10] used the mixture of (concrete waste and asphalt waste) as addition to the gypseous soil, they found that, the values of cohesion and angle of internal friction increase with the increase of concrete wastes, in which the cohesion increases in a magnitude of 100% and angle of internal friction in a magnitude of 14%, the value 8% represents the optimum percentages. When asphalt mixture wastes are added, the cohesion increases in a magnitude of 112% with a decrease in the angle of internal friction in a magnitude of 2% and the optimum percentage is 108% with an increase in the angle of internal friction in a magnitude of 14%.…”
Section: Plate (1) Individual Footingsmentioning
confidence: 99%
“…Thus, physical traits evaluation of asphalt is primary. On the other hand, polymers/asphalt mixes within expand domain of contents and kinds perform good implementation in the design of flexible concrete pavements [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Polyethylene (PE) and polypropylene (PP) are worldwide used polymers in paving applications. Thus, PP was used in this research due to its lower price and added content.…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum mineral also known in its chemical formula CaSO 4 .2H 2 O is hydrated calcium sulfate with moderate solubility [3].Several researchers tackled the improvement for gypseous. Some methods involve mixing additives such as cement [4,5], lime [6], and concrete/asphalt waste mixture [7]. However, breaking the gypseous bonds leads to reduction in soil strength.…”
mentioning
confidence: 99%
“…Several researchers tackled the improvement for gypseous. Some methods involve mixing additives such as cement [4,5], lime [6], and concrete/asphalt waste mixture [7]. However, breaking the gypseous bonds leads to reduction in soil strength.…”
mentioning
confidence: 99%